The Cambridge handbook of child language - Bavin, Edith Laura (Cambridge handbooks in linguistics., 2009)
A one-stop resource for the field of language acquisition and development. The handbook surveys statistical learning, the cross-linguistic study of language acquisition, pre-linguistic development, and topics in semantic, pragmatic and narrative development, among other topics.